The Polish Teachers’ Union in the Process of Preparing Teachers for Educational Practice in Poland after the Second World War - Kahl, Edyta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
The paper is dedicated to the problems of the participation of the ZNP (Związek Nauczycielstwa Polskiego – The Association of Polish Teachers) in the process of the preparation of teachers for the educational tasks after WWII. The author presents the conditions of the changes of the political system, the stages of the ideological and politicaltakeover of this teachers’ organisation, and the symptoms of the influence of various unions on the teaching environment that was aimed to instil the scientific worldview and to prepare the teachers to implement the goals and the tasks of socialist education.
Keywords: education; education policy; teachers; Polish Teachers Union; political authorities; education authorities